A Double‐Blind, Placebo‐Controlled Study of Repetitive Transnasal Sphenopalatine Ganglion Blockade With Tx360® as Acute Treatment for Chronic Migraine. Issue 1 (23rd October 2014) - Cady, Roger; Saper, Joel; Dexter, Kent; Manley, Heather R.
<x xml:space="preserve">Abstract</x> Objective To determine if repetitive sphenopalatine ganglion (SPG) blocks with 0.5% bupivacaine delivered through the Tx360® are superior in reducing pain associated with chronic migraine (CM) compared with saline. Background The SPG is a small concentrated structure of neuronal tissue that resides within the pterygopalatine fossa (PPF) in close proximity to the sphenopalatine foramen and is innervated by the maxillary division of the trigeminal nerve. From an anatomical and physiological perspective, SPG blockade may be an effective acute and preventative treatment for CM. Method This was a double‐blind, parallel‐arm, placebo‐controlled, randomized pilot study using a novel intervention for acute treatment in CM. Up to 41 subjects could be enrolled at 2 headache specialty clinics in the US. Eligible subjects were between 18 and 80 years of age and had a history of CM defined by the second edition of the International Classification of Headache Disorders appendix definition. They were allowed a stable dose of migraine preventive medications that was maintained throughout the study. Following a 28‐day baseline period, subjects were randomized by computer‐generated lists of 2:1 to receive 0.5% bupivacaine or saline, respectively. The primary end‐point was to compare numeric rating scale scores at pretreatment baseline vs 15 minutes, 30 minutes, and 24 hours postprocedure for all 12 treatments. SPG blockade was accomplished with the Tx360®, which allows a small flexible soft plastic tube that is advanced below the middle turbinate just past the pterygopalatine fossa into the intranasal space. A 0.3 cc of anesthetic or saline was injected into the mucosa covering the SPG. The procedure is performed similarly in each nostril. The active phase of the study consisted of a series of 12 SPG blocks with 0.3 cc of 0.5% bupivacaine or saline provided 2 times per week for 6 weeks. Subjects were re‐evaluated at 1 and 6 months postfinal procedure. Results The final dataset included 38 subjects, 26 in the bupivacaine group and 12 in the saline group. A repeated measures analysis of variance showed that subjects receiving treatment with bupivacaine experienced a significant reduction in the numeric rating scale scores compared with those receiving saline at baseline (M = 3.78 vs M = 3.18, P = .10), 15 minutes (M = 3.51 vs M = 2.53, P < .001), 30 minutes (M = 3.45 vs M = 2.41, P < .001), and 24 hours after treatment (M = 4.20 vs M = 2.85, P < .001), respectively. Headache Impact Test‐6 scores were statistically significantly decreased in subjects receiving treatments with bupivacaine from before treatment to the final treatment (Mdiff = −4.52, P = .005), whereas no significant change was seen in the saline group (Mdiff = −1.50, P = .13). Conclusion SPG blockade with bupivacaine delivered repetitively for 6 weeks with the Tx360® device demonstrates promise as an acute treatment of headache in some subjects with CM. Statistically significant headache relief is noted at 15 and 30 minutes and sustained at 24 hours for SPG blockade with bupivacaine vs saline. The Tx360® device was simple to use and not associated with any significant or lasting adverse events. Further research on sphenopalatine ganglion blockade is warranted.